Pengaruh Kebijakan Dividen, Kepemilikan Manajerial, Penghindaran Pajak, Profitabilitas, Dan Leverage Terhadap Nilai Perusahaan - Ratnandari, Nindita Indah; Kusumawati, Eny (Politeknik Negeri Ambon, 2023)
The firm value measures the amount of a company's stock market price against its book value as an illustration of investors' perceptions of their confidence in the company for good performance prospects in the future. This study aims to analyze the effect of dividend policy, managerial ownership, tax avoidance, profitability, and leverage on firm value in non-financial companies on the Indonesia Stock Exchange for the period 2020 - 2022. The sampling technique used in this study was purposive sampling. This research sample consists of 165 companies that meet the criteria as a unit of analysis. The analysis method used is multiple linear regression analysis. The results provide empirical evidence that dividend policy, managerial ownership, profitability, and leverage affect firm value. Meanwhile, tax avoidance does not affect firm value.